2011
DOI: 10.1111/j.1365-2672.2011.04959.x
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment, isolation and characterization of fungi tolerant to 1-ethyl-3-methylimidazolium acetate

Abstract: Aims:  This work aimed to characterize microbial tolerance to 1‐ethyl‐3‐methylimidazolium acetate ([C2mim][OAc]), an ionic liquid that has emerged as a novel biomass pretreatment for lignocellulosic biomass. Methods and Results:  Enrichment experiments performed using inocula treated with [C2mim][OAc] under solid and liquid cultivation yielded fungal populations dominated by Aspergilli. Ionic liquid‐tolerant Aspergillus isolates from these enrichments were capable of growing in a radial plate growth assay in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…However, to date there are only few studies that have investigated IL tolerant microorganisms found in nature and identified metabolic pathways responsible for IL tolerance. Recently, enrichment cultures have been applied for discovering IL tolerant microorganisms from environmental samples by generating less complex lignocellulolytic microbial communities and facilitating the discovery of potential enzymes and microorganisms for biomass deconstruction (Pace et al 2016;Reddy et al 2012;Simmons et al 2014;Singer et al 2011). However, further studies on IL tolerant microbial communities using metagenomic and metatranscriptomic analyses are needed to understand how organisms in a community work synergistically to tolerate ILs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date there are only few studies that have investigated IL tolerant microorganisms found in nature and identified metabolic pathways responsible for IL tolerance. Recently, enrichment cultures have been applied for discovering IL tolerant microorganisms from environmental samples by generating less complex lignocellulolytic microbial communities and facilitating the discovery of potential enzymes and microorganisms for biomass deconstruction (Pace et al 2016;Reddy et al 2012;Simmons et al 2014;Singer et al 2011). However, further studies on IL tolerant microbial communities using metagenomic and metatranscriptomic analyses are needed to understand how organisms in a community work synergistically to tolerate ILs.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms displaying IL tolerance have been screened using direct plating, growth in liquid culture and phenotypic microarrays (Deive et al 2011;Khudyakov et al 2012;Liu et al 2015;Nakashima et al 2011;Petkovic et al 2009;Petkovic et al 2010;Santos et al 2014;Simmons et al 2014;Singer et al 2011;Sitepu et al 2014).…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…Recently, a strain of the thermotolerant fungus Aspergillus fumigatus was grown on switchgrass in the presence of 5% 1-butyl-3-methylimidazolium chloride, abbreviated as [C 4 mim]Cl, secreting high amounts of cellulase and hemicellulase enzymes. These GHs were shown to retain residual activity in up to 20% [C 4 mim]Cl [9]. In addition, increased IL tolerance has been demonstrated for thermophilic glycoside hydrolases from bacteria [10,11] and archaea [12], suggesting a correlation between thermotolerance and IL tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is crucial to identify IL-resistant cellulase and microorganism for digesting cellulose that can tolerate residual levels (0.2-5% w/v) of ILs in the regenerated biomass (Ruegg et al, 2013). Nowadays, identifying metabolic pathways that confer tolerance of microbes to ILs and IL-tolerant enzymes has become an active area of research (Singer et al, 2011). A few IL stable cellulases derived from metagenome as well as from culturable microbes such as Penicillium janthinellum, Thermatoga maritime, Pyrococcus horikoshii, and Halorhabdus utahensis have been reported (Trivedi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%